Artificial Intelligence in Islamic Finance: Maintaining Islamic Ethics with the Maqasid al-Shariah Framework - Harits, Muhammad; Isman, Isman (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyse the application of AI in Islamic economics, identify emerging ethical challenges, and offer a maqasid al-shariah-based framework as a guide for sharia-compliant AI implementation. Methodology: The method used is a qualitative approach through a literature review to examine previous studies on the integration of AI in Islamic finance. Results: The results show that AI can improve operational efficiency, reduce costs, and expand access to Islamic financial services, especially for the unbanked and underbanked. However, the application of AI faces difficulties in aligning algorithms with sharia principles, particularly in terms of fairness and strict sharia supervision. Applications/Originality/Value: The novelty of this study is the proposal of a conceptual framework based on maqasid al-shariah that can ensure the ethical application of AI in accordance with Islamic values.